Laminated aluminum electrolytic capacitor and preparation method thereof

By depositing alumina film using a metal sputtering process on the surface of the aluminum foil, combined with multi-step heat treatment and quenching treatment, the problem of insufficient density of alumina film in the prior art is solved, and the low leakage current and long life of the stacked aluminum electrolytic capacitor is achieved.

CN119517626APending Publication Date: 2025-02-25ZHAOQING BERYL ELECTRONICS TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411630430.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The pore density of the alumina films in the existing laminated aluminum electrolytic capacitors is not dense and uniform enough, resulting in a large leakage current and affecting the service life of the product.

Method used

Alumina film is deposited on the surface of the aluminum foil by metal sputtering process, and multi-step heat treatment and quenching treatment are carried out to form a uniform, flat and dense alumina film.

Benefits of technology

It significantly reduces the leakage current of the laminated aluminum electrolytic capacitor, extends the service life of the product, and improves the resistance to corrosion in the external environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a laminated aluminum electrolytic capacitor and a preparation method thereof. The preparation method comprises the following steps: S100, cutting an aluminum foil; s200, depositing on the surface of the aluminum foil through metal sputtering to form an aluminum oxide film; s300, the sputtered aluminum foil is subjected to multi-step heat treatment and quenching treatment; s400, depositing a conductive polymer on the aluminum oxide to serve as a cathode of the capacitor; s500, covering the conductive polymer with a graphite layer; s600, covering the graphite layer with a silver paste layer; s700, stacking a plurality of aluminum foils coated with the silver paste layers together to form a laminated capacitor structure; and S800, packaging and aging are carried out. The aluminum oxide film formed on the aluminum foil of the laminated aluminum electrolytic capacitor provided by the invention is uniform, flat and compact, the laminated aluminum electrolytic capacitor is small in leakage current and long in service life, and the leakage current of the laminated aluminum electrolytic capacitor cannot be obviously increased along with the increase of service time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum electrolytic capacitors, and more specifically, to a laminated aluminum electrolytic capacitor and a preparation method thereof. Background Art

[0002] The laminated aluminum capacitor is a new type of solid-state capacitor with a multilayer structure design that can provide higher capacitance in a smaller volume. Laminated aluminum capacitors have lower equivalent series resistance (ESR), good high-frequency characteristics, higher ripple current tolerance and excellent high-temperature performance, which have significant advantages over traditional winding capacitors.

[0003] The anode and cathode structure of the laminated aluminum capacitor mainly includes anode aluminum foil, dielectric and cathode material. The anode of the aluminum electrolytic capacitor is usually made of aluminum foil. There is a dense and non-porous aluminum oxide film on the surface of the anode foil. The aluminum oxide film acts as a dielectric in the capacitor and plays a role in voltage resistance. Its properties determine the capacitance and life of the aluminum electrolytic capacitor.

[0004] At present, the aluminum oxide film of the laminated aluminum electrolytic capacitor is usually produced by subjecting the aluminum foil to a corrosion process and a chemical formation process. The chemical formation process is to place the aluminum foil in a chemical solution of a specific temperature, pH value and concentration, and gradually form an oxide film by applying different levels of current and voltage. The pore density of the aluminum oxide film produced by the chemical formation process is not dense and uniform enough, resulting in a large leakage current of the laminated aluminum electrolytic capacitor. The leakage current increases more significantly after being placed for a period of time, which seriously affects the service life of the product and cannot meet the technical requirements of the rapidly developing electronic and electrical market.

[0005] For example, Chinese patent application 202211734744.7 discloses a method for preparing an ultra-low ESR laminated aluminum solid-state aluminum electrolytic capacitor, and the method steps are as follows: S1: aluminum foil cutting and punching; S2: welding the punched aluminum foil to the Bar strip; S3: chemical formation and impregnation; S4: wrapping the polymer cathode layer of the impregnated capacitor with a layer of conductive carbon, solidifying it, coating it with silver, and wrapping the carbon layer with a layer of silver, solidifying it, to obtain a very flat monolithic capacitor chip; S5: stacking the monolithic capacitor chip impregnated with carbon in S4 on a lower lead frame, the cathode part is connected by coating with conductive silver glue, solidified, and the positive part is laser welded; the lower lead frame includes a frame, and a number of positioning holes and reference cavities are opened on both sides of the frame, and a first connecting plate and a second connecting plate are arranged on both sides of the reference cavity, and a convex strip is fixedly arranged below one end of the first connecting plate, and a concave plate is fixedly arranged at one end of the second connecting plate. In this patent, the aluminum oxide film is generated by chemical formation, and the density of the film cannot be guaranteed.

[0006] Therefore, there is an urgent need to develop a laminated aluminum electrolytic capacitor with uniform aluminum oxide film and high density. Summary of the invention

[0007] Based on this, it is necessary to provide a laminated aluminum electrolytic capacitor with dense and uniform aluminum oxide film and a preparation method thereof to address the above technical problems, reduce the leakage current of the laminated aluminum electrolytic capacitor, and increase the service life.

[0008] In order to solve the above technical problems, the present invention provides a laminated aluminum electrolytic capacitor with a dense and uniform aluminum oxide film, which adopts the following technical solution:

[0009] A first aspect of the present invention provides a method for preparing a laminated aluminum electrolytic capacitor, comprising the following steps:

[0010] S100: cutting of aluminum foil;

[0011] S200: forming an aluminum oxide film by metal sputtering on the surface of the aluminum foil;

[0012] S300: subjecting the sputtered aluminum foil to multi-step heat treatment and quenching treatment;

[0013] S400: Deposition of a conductive polymer on aluminum oxide as the cathode of the capacitor;

[0014] S500: Graphite layer on conductive polymer;

[0015] S600: Covering the graphite layer with a silver paste layer;

[0016] S700: Multiple pieces of aluminum foil coated with silver paste are stacked together to form a stacked capacitor structure;

[0017] S800: Encapsulation and aging.

[0018] Furthermore, the thickness of the aluminum oxide film in step S200 is 0.01-0.05 mm.

[0019] Furthermore, the conductive polymer in step S400 is any one of polyaniline conductive polymer, polypyrrole conductive polymer and polythiophene conductive polymer.

[0020] Furthermore, the quenching medium used in the quenching treatment in step 300 is silicone oil.

[0021] Furthermore, the thickness of the graphite layer in step 500 is 0.01-0.2 mm.

[0022] Furthermore, the thickness of the silver paste layer in step 600 is 0.01-0.2 mm.

[0023] Furthermore, the temperature of the multi-step temperature heat treatment in step 300 is 100°C to 300°C.

[0024] Furthermore, the aging temperature in the aging step of step S800 is 40 to 155° C., and the aging time is 1 to 24 hours.

[0025] Furthermore, the metal sputtering in step S200 includes:

[0026] S210, place the aluminum oxide and aluminum foil in a vacuum chamber at a temperature of 45℃~55℃ and an air pressure of 10 -6 Pa~10 -9 Pa;

[0027] S220, metal sputtering is completed using a metal film sputtering instrument. The instrument parameters are set as follows: gas pressure is 10 - 3 mbar~1mbar, the distance between the alumina target and the aluminum foil substrate is 1cm~5cm, the substrate bias is -100V~-500V, the sputtering current is 80mA~120mA, the DC power supply output voltage is 550V~650V, the magnetic field strength is 50 Gauss~200 Gauss, the ion energy is 500eV~2000eV, and the ion current density is 0.5mA / cm 2 ~1mA / cm 2 , the sputtering time is 5min~10min;

[0028] S230. The sputtered aluminum oxide atoms or molecules are deposited on the surface of the aluminum foil to form a porous aluminum oxide film with a thickness of 0.01 to 0.05 mm.

[0029] A second aspect of the present invention provides a multilayer aluminum electrolytic capacitor, which is manufactured by any of the above methods.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The method for preparing a laminated aluminum electrolytic capacitor provided by the present invention deposits aluminum oxide on the surface of an aluminum foil through a metal sputtering process to form a uniform, flat and dense aluminum oxide film, thereby improving the thermal stability and external environmental corrosion resistance of the aluminum foil, performing multi-step temperature heat treatment under vacuum conditions and placing the heat-treated aluminum foil in silicone oil for quenching treatment, thereby further improving the temperature characteristics and stability of the aluminum foil. The laminated aluminum electrolytic capacitor prepared by the method of the present invention has a small leakage current and a long service life, and its leakage current will not increase significantly with the increase of usage time. DETAILED DESCRIPTION

[0032] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0033] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application is clearly and completely described below.

[0034] Example 1

[0035] This embodiment provides a laminated aluminum electrolytic capacitor and a method for preparing the same, which comprises the following steps:

[0036] S100: Cut aluminum foil with a purity of 99% into corresponding sizes;

[0037] S200: forming an aluminum oxide film by metal sputtering on the surface of the aluminum foil;

[0038] S300: subjecting the sputtered aluminum foil to multi-step heat treatment and quenching treatment;

[0039] S400: depositing a conductive polymer on aluminum oxide as a cathode of the capacitor, wherein the conductive polymer is a polypyrrole conductive polymer;

[0040] S500: Covering the conductive polymer with a graphite layer, wherein the thickness of the graphite layer is 0.01 mm;

[0041] S600: Covering the graphite layer with a silver paste layer, wherein the thickness of the silver paste layer is 0.01 mm;

[0042] S700: Multiple pieces of aluminum foil coated with silver paste are stacked together to form a stacked capacitor structure;

[0043] S800: Encapsulation and aging.

[0044] Furthermore, the step 200 includes steps 210 to 230:

[0045] S210, place the aluminum oxide and aluminum foil in a vacuum chamber at a temperature of 45°C and an air pressure of 10 -6 Pa;

[0046] S220, applying voltage between the aluminum oxide and the aluminum foil to generate plasma, the ions in the plasma are accelerated and bombard the aluminum oxide, so that atoms or molecules on the surface of the aluminum oxide are sputtered out; specifically, in this step, a metal film sputtering instrument is used to complete metal sputtering, and the instrument parameters are set as follows: gas pressure is 10-3 mbar, the distance between the alumina target and the aluminum foil substrate is 1 cm, the substrate bias is -100 V, the sputtering current is 80 mA, the DC power supply output voltage is 550 V, the magnetic field strength is 50 Gauss, the ion energy is 500 eV, and the ion current density is 0.5 mA / cm 2 , the sputtering time is 5min;

[0047] S230. The sputtered aluminum oxide atoms or molecules are deposited on the surface of the aluminum foil to form a uniform and flat porous aluminum oxide film with a thickness of 0.03 mm.

[0048] Furthermore, the step 300 includes steps 310 to 320:

[0049] S310, subjecting the sputtered aluminum foil to a multi-step heat treatment in a vacuum state: starting from 100°C, increasing the temperature step by step to 200°C with a temperature of 20°C as a step, and keeping each step for 600s;

[0050] S320, placing the aluminum foil after the multi-step heat treatment into water for quenching treatment and cooling to room temperature.

[0051] Furthermore, the step S700 specifically comprises stacking together multiple pieces of aluminum foil coated with a silver paste layer using a conductive paste to form a laminated capacitor structure. In this embodiment, a 6-layer laminated structure is formed. Multiple pieces of aluminum foil can also be stacked by other conventional methods such as motor welding, laser welding, and riveting.

[0052] Furthermore, the step S800 includes steps S810 and S820:

[0053] S810, welding the anode region of the stacked capacitor structure to the anode of the lead frame, bonding the cathode region of the stacked capacitor structure to the cathode of the lead frame with a conductive silver paste, and encapsulating the entire stacked capacitor structure with an epoxy resin to form a stacked aluminum electrolytic capacitor;

[0054] S820, performing aging treatment on the laminated aluminum electrolytic capacitor, wherein the aging temperature is 40° C., the aging voltage is the rated voltage, and the aging time is 24 hours.

[0055] Example 2

[0056] This embodiment provides a laminated aluminum electrolytic capacitor and a method for preparing the same, which comprises the following steps:

[0057] S100: Cut aluminum foil with a purity of 95% into corresponding sizes;

[0058] S200: forming an aluminum oxide film by metal sputtering on the surface of the aluminum foil;

[0059] S300: subjecting the sputtered aluminum foil to multi-step heat treatment and quenching treatment;

[0060] S400: depositing a conductive polymer on aluminum oxide as a cathode of the capacitor, wherein the conductive polymer is a polyaniline conductive polymer;

[0061] S500: covering the conductive polymer with a graphite layer, wherein the thickness of the graphite layer is 0.1 mm;

[0062] S600: Covering the graphite layer with a silver paste layer, wherein the thickness of the silver paste layer is 0.1 mm;

[0063] S700: Multiple pieces of aluminum foil coated with silver paste are stacked together to form a stacked capacitor structure;

[0064] S800: Encapsulation and aging.

[0065] Furthermore, the step 200 includes steps 210 to 230:

[0066] S210, place the aluminum oxide and aluminum foil in a vacuum chamber at a temperature of 50°C and an air pressure of 10 -8 Pa;

[0067] S220, applying voltage between the aluminum oxide and the aluminum foil to generate plasma, the ions in the plasma are accelerated and bombard the aluminum oxide, so that atoms or molecules on the surface of the aluminum oxide are sputtered out; specifically, in this step, a metal film sputtering instrument is used to complete metal sputtering, and the instrument parameters are set as follows: gas pressure is 10 -1 mbar, the distance between the target and the substrate is 3 cm, the substrate bias is -200 V, the sputtering current is 100 mA, the DC power supply output voltage is 600 V, the magnetic field strength is 100 Gauss, the ion energy is 1000 eV, and the ion current density is 0.7 mA / cm 2 , the sputtering time is 7min;

[0068] S230. The sputtered aluminum oxide atoms or molecules are deposited on the surface of the aluminum foil to form a uniform and flat porous aluminum oxide film with a thickness of 0.01 mm.

[0069] Furthermore, the step 300 includes steps 310 to 320:

[0070] S310, subjecting the sputtered aluminum foil to a multi-step heat treatment in a vacuum state: starting from 100°C, the temperature is gradually increased to 160°C in steps of 20°C, and each step is kept for 600s;

[0071] S320, placing the aluminum foil after the multi-step heat treatment into quenching oil for quenching treatment and cooling to room temperature.

[0072] Furthermore, the step S700 specifically involves stacking together multiple pieces of aluminum foil coated with a silver paste layer using a conductive paste to form a stacked capacitor structure. In this embodiment, a 6-layer stacked structure is formed.

[0073] Furthermore, the step S800 includes steps S810 and S820:

[0074] S810, welding the anode region of the stacked capacitor structure to the anode of the lead frame, bonding the cathode region of the stacked capacitor structure to the cathode of the lead frame with a conductive silver paste, and encapsulating the entire stacked capacitor structure with an epoxy resin to form a stacked aluminum electrolytic capacitor;

[0075] S820, performing aging treatment on the laminated aluminum electrolytic capacitor, wherein the aging temperature is 100° C., the aging voltage is the rated voltage, and the aging time is 12 hours.

[0076] Example 3

[0077] This embodiment provides a laminated aluminum electrolytic capacitor and a method for preparing the same, which comprises the following steps:

[0078] S100: Cut aluminum foil with a purity of 90% into corresponding sizes;

[0079] S200: forming an aluminum oxide film by metal sputtering on the surface of the aluminum foil;

[0080] S300: subjecting the sputtered aluminum foil to multi-step heat treatment and quenching treatment;

[0081] S400: depositing a conductive polymer on aluminum oxide as a cathode of the capacitor, wherein the conductive polymer is a polythiophene conductive polymer;

[0082] S500: covering the conductive polymer with a graphite layer, wherein the thickness of the graphite layer is 0.2 mm;

[0083] S600: Covering the graphite layer with a silver paste layer, wherein the thickness of the silver paste layer is 0.2 mm;

[0084] S700: Multiple pieces of aluminum foil coated with silver paste are stacked together to form a stacked capacitor structure;

[0085] S800: Encapsulation and aging.

[0086] Furthermore, the step 200 includes steps 210 to 230:

[0087] S210, place the aluminum oxide and aluminum foil in a vacuum chamber at a temperature of 55°C and an air pressure of 10 -9 Pa;

[0088] S220, applying voltage between aluminum oxide and aluminum foil to generate plasma, the ions in the plasma are accelerated and bombard the aluminum oxide, so that atoms or molecules on the surface of the aluminum oxide are sputtered out; specifically, in this step, a metal film sputtering instrument is used to complete metal sputtering, and the instrument parameters are set as follows: gas pressure is 1 mbar, the distance between the target and the substrate is 5 cm, the substrate bias is -500 V, the sputtering current is 120 mA, the DC power supply output voltage is 650 V, the magnetic field strength is 200 Gauss, the ion energy is 2000 eV, and the ion current density is 1 mA / cm 2 , the sputtering time is 10min;

[0089] S230. The sputtered aluminum oxide atoms or molecules are deposited on the surface of the aluminum foil to form a uniform and flat porous aluminum oxide film with a thickness of 0.05 mm.

[0090] Furthermore, the step 300 includes steps 310 to 320:

[0091] S310, subjecting the sputtered aluminum foil to a multi-step heat treatment in a vacuum state: starting from 100°C, increasing the temperature step by step to 300°C in 20°C steps, and keeping each step for 300s;

[0092] S320, placing the aluminum foil after the multi-step heat treatment into silicone oil for quenching treatment and cooling to room temperature.

[0093] Furthermore, the step S700 specifically involves stacking together multiple pieces of aluminum foil coated with a silver paste layer using a conductive paste to form a stacked capacitor structure. In this embodiment, a 6-layer stacked structure is formed.

[0094] Furthermore, the step S800 includes steps S810 and S820:

[0095] S810, welding the anode region of the stacked capacitor structure to the anode of the lead frame, bonding the cathode region of the stacked capacitor structure to the cathode of the lead frame with a conductive silver paste, and encapsulating the entire stacked capacitor structure with an epoxy resin to form a stacked aluminum electrolytic capacitor;

[0096] S820, performing aging treatment on the laminated aluminum electrolytic capacitor, wherein the aging temperature is 155° C., the aging voltage is the rated voltage, and the aging time is 1 hour.

[0097] Comparative Example 1

[0098] This comparative example provides a laminated aluminum electrolytic capacitor and a preparation method thereof, which differs from Example 1 in that: a conventional chemical formation method is used to generate an aluminum oxide film instead of steps S2 to S6 in Example 1: an aluminum foil is placed in a chemical formation liquid at 40° C., and an aluminum oxide film with a thickness of 0.03 mm is gradually formed by applying its rated voltage. The chemical formation liquid is conventional boric acid (H3BO 3) and glycerol (glycerol, C3H8O3) mixed solution, which is prepared by the following components in volume ratio: 3% boric acid (H3BO3), 8% glycerol (glycerol, C3H8O3), and 89% deionized water.

[0099] The LC values ​​of the capacitors prepared by the methods of Examples 1 to 3 and Comparative Example 1 were verified and tested during use, and the results are shown in Table 1 below. The leakage current value is measured after charging for 2 minutes at the rated voltage.

[0100] Table 1: Leakage current detection results of each embodiment and comparative example 1

[0101]

[0102] From the test results, it can be seen that the multilayer aluminum electrolytic capacitors prepared by Examples 1 to 3 have stable leakage current performance. Compared with the multilayer aluminum electrolytic capacitors produced by the traditional method in Comparative Example 1, the leakage current is greatly reduced during application.

[0103] Obviously, the embodiments described above are only a part of the embodiments of the present application, rather than all of the embodiments. The present application can be implemented in many different forms. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Although the present application is described in detail with reference to the aforementioned embodiments, for those skilled in the art, it is still possible to modify the technical solutions recorded in the aforementioned specific implementation methods, or to perform equivalent replacement of some of the technical features therein. Any equivalent structure made using the contents of the specification of this application, directly or indirectly used in other related technical fields, is similarly within the scope of patent protection of this application.

Claims

1. A method for preparing a laminated aluminum electrolytic capacitor, characterized in that: The following steps are involved: S100: cutting of aluminum foil; S200: forming an aluminum oxide film by metal sputtering on the surface of the aluminum foil; S300: subjecting the sputtered aluminum foil to multi-step heat treatment and quenching treatment; S400: Deposition of a conductive polymer on aluminum oxide as the cathode of the capacitor; S500: Graphite layer on conductive polymer; S600: Covering the graphite layer with a silver paste layer; S700: Multiple pieces of aluminum foil coated with silver paste are stacked together to form a stacked capacitor structure; S800: Encapsulation and aging.

2. The method for preparing a laminated aluminum electrolytic capacitor according to claim 1, characterized in that: The thickness of the aluminum oxide film in step S200 is 0.01-0.05 mm.

3. The method for preparing a laminated aluminum electrolytic capacitor according to claim 1, characterized in that: The conductive polymer in step S400 is any one of polyaniline conductive polymer, polypyrrole conductive polymer and polythiophene conductive polymer.

4. The method for preparing a laminated aluminum electrolytic capacitor according to claim 1, characterized in that: The quenching medium used in the quenching treatment of step 300 is silicone oil.

5. The method for preparing a laminated aluminum electrolytic capacitor according to claim 1, characterized in that: The thickness of the graphite layer in step 500 is 0.01-0.2 mm.

6. The method for preparing a laminated aluminum electrolytic capacitor according to claim 1, characterized in that: The thickness of the silver paste layer in step 600 is 0.01-0.2 mm.

7. The method for preparing a laminated aluminum electrolytic capacitor according to claim 1, characterized in that: The temperature of the multi-step temperature heat treatment in step 300 is 100° C. to 300° C.

8. The method for preparing a laminated aluminum electrolytic capacitor according to claim 1, characterized in that: The aging temperature in the aging step S800 is 40 to 155° C., and the aging time is 1 to 24 hours.

9. The method for preparing a laminated aluminum electrolytic capacitor according to claim 2, characterized in that: The metal sputtering in step S200 includes: S210, place the aluminum oxide and aluminum foil in a vacuum chamber at a temperature of 45℃~55℃ and an air pressure of 10 -6 Pa~10 -9 Pa; S220, metal sputtering is completed using a metal film sputtering instrument. The instrument parameters are set as follows: gas pressure is 10 -3 mbar~1mbar, the distance between the alumina target and the aluminum foil substrate is 1cm~5cm, the substrate bias is -100V~-500V, the sputtering current is 80mA~120mA, the DC power supply output voltage is 550V~650V, the magnetic field strength is 50 Gauss~200 Gauss, the ion energy is 500eV~2000eV, and the ion current density is 0.5mA / cm 2 ~1mA / cm 2 , the sputtering time is 5min~10min; S230. The sputtered aluminum oxide atoms or molecules are deposited on the surface of the aluminum foil to form a porous aluminum oxide film with a thickness of 0.01 to 0.05 mm.

10. A laminated aluminum electrolytic capacitor, characterized in that: It is prepared by any one of the methods described in claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of ultra-low ESR laminated aluminum solid aluminum electrolytic capacitor

    CN116092832A